Identification and assessment of geohazards affecting pipelines and urban areas; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Strokova L. A. Ludmila Aleksandrovna (Geoecology and Environmental Protection, 2016)
Title screen